The effect of remuneration schedule on data completion and retention in the pregnancy eating attributes study (PEAS) - Terry, Ndeah (PLoS One, 2021)
Maximizing data completion and study retention is essential in population research. This study examined the effect of remuneration schedule and data collection modality on data completion and retention in the Pregnancy Eating Attributes Study cohort. Participants (n = 458) completed online surveys and attended six in-person study visits. Initially, remuneration was a prespecified amount per visit, then was changed mid-study to be prorated based on the number of forms completed. Additionally, survey data collection modality was changed to in-person at the sixth study visit. In this secondary data analysis, there was no effect of remuneration schedule on withdrawal rates or time-to-withdrawal. Survey completion was significantly lower under prorated remuneration at the first visit but did not significantly differ at subsequent visits. The lump sum group had significantly greater odds of completely the first and second trimester dietary record (OR = 4.1, OR = 2.6, respectively) then the prorated group but were almost half as likely to complete the dietary record at the 6-month postpartum visit (OR = 0.5). Survey completion at sixth visit was significantly higher for in-person versus online completion (68.6% vs. 93.1%). Findings suggest that remuneration schedule and data collection modality can impact completion of self- reported assessments.